Knowledge, Commitment and Compliance of Barangay Focal Persons on Gender and Development: Basis For An Action Plan (International Journal of Scientific Research and Management (IJSRM), 2023)
This study aimed to determine the level of knowledge, level of commitment, and extent of compliance of focal persons on the Gender and Development Program from the 61 barangays in Bacolod City for the Fiscal Year 2021 as basis for an enhancement program. The study employed a descriptive design. The respondents of the study were the 160 focal persons of all barangays of Bacolod City. The data gathering instrument was a self-made questionnaire. Descriptive, comparative analytical, relational analytical schemes were employed to determine the objectives of the study. The statistical tools used were Frequency count and Percentage, Mean Mann-Whitney U test, and Spearman Rho. Based on the findings, the researcher has come up with the following conclusions. Respondents in Bacolod City were dominated by the older group aging 42 years old, and the above majority were high school graduates and mostly serving in longer years for more than 13 years as barangay officials in the city. Generally, the level of knowledge of focal persons on the Gender and Development Program is high. Overall, focal persons have a high level of commitment to the Gender and Development Program. The extent of compliance of focal persons on the Gender and Development Program is generally to a great extent, particularly in the conduct of advocacy and promoting the activities of GAD programs. The level of knowledge of focal persons on the Gender and Development Program when grouped and compared according to age, educational attainment, and length of service were generally high. The level of commitment of focal persons on the gender and Development program is generally high when grouped and compared to their age, educational attainment, and length of service. This concludes that barangay officials adopt and implement actions to protect and promote GAD programs in their respective barangays in the city. The barangay officials’ extent of compliance when grouped and compared according to age, educational attainment, and service length are great. There was no significant difference in the level of knowledge of barangay officials on gender development programs when they are grouped according to age, educational attainment, and length of service. Responses of the barangay officials on the level of commitment on the Gender and Development Programs are the same since no significant difference was found in the level of commitment when they are grouped according to their age, educational attainment, and length of service. There is no significant difference in the extent of compliance of focal persons on the Gender and Development program when they were grouped according to age, educational attainment, and length of service. The level of knowledge on the Gender and Development Program was influenced by the extent of compliance of the barangay officials on the Gender and Development Program. Likewise, the level of commitment of the barangay officials to the Gender and Development Program is influenced by the extent of their compliance. Finally, the level of commitment is affected by the level of knowledge of focal persons on the Gender and Development Program, which concludes that the more orientation conducted about the GAD program. An action plan was developed as an enhancement program for the focal persons on Gender and Development program in different barangays in Bacolod City.